# Find the derivative of the following function. \[y={{\log }_{3}}x-{{\log }^{-1}}{{3}^{-1}}\times \log {{x}^{-1}}\]

Answer

Verified

365.1k+ views

Hint: To find the derivative of the function given in the question, one must start by

simplifying the given function using properties of logarithmic function and then differentiating the terms given in the function using sum and product rule of differentiation.

To find the derivative of the function\[y={{\log }_{3}}x-{{\log }^{-1}}{{3}^{-1}}\times \log {{x}^{-1}}\], we will differentiate it with respect to the variable\[x\]using some logarithmic properties.

We will first simplify the given function.

We know that\[{{\log }_{b}}a=\dfrac{\log a}{\log b}\].

Substituting\[a=x,b=3\]in the above equation, we get\[{{\log }_{3}}x=\dfrac{\log x}{\log 3}\]. \[...(1)\]

We also know that\[{{\log }^{-1}}a=\dfrac{1}{\log a}\]. \[...(2)\]

Substituting\[a={{3}^{-1}}\], we get\[{{\log }^{-1}}{{3}^{-1}}=\dfrac{1}{\log {{3}^{-1}}}\].

\[...(3)\]

We know that\[\log {{a}^{-1}}=-\log a\].

Thus, we have\[\dfrac{1}{\log {{3}^{-1}}}=\dfrac{1}{-\log 3}\].

Merging the above equation with equation\[(3)\], we get\[{{\log }^{-1}}{{3}^{-1}}=\dfrac{1}{\log {{3}^{-1}}}=\dfrac{1}{-\log 3}\]. \[...(4)\]

Substituting\[a=x\]in equation\[(2)\], we get\[\log {{x}^{-1}}=-\log x\]. \[...(5)\]

Substituting equation\[(1)\], \[(4)\]and\[(5)\]in the given equation\[y={{\log }_{3}}x-{{\log }^{-1}}{{3}^{-1}}\times \log {{x}^{-1}}\], we get\[y={{\log }_{3}}x-{{\log }^{-1}}{{3}^{-1}}\times

\log {{x}^{-1}}=\dfrac{\log x}{\log 3}-\left( \dfrac{1}{-\log 3} \right)-\log x\].

Simplifying the above equation, we get\[y=\dfrac{\log x}{\log 3}-\dfrac{\log x}{\log 3}=0\].

We know that the differentiation of a constant function with respect to any variable is 0.

Thus, we have\[\dfrac{dy}{dx}=0\]as\[y=0\].

We get the derivative of the given function 0 as by simplifying the function, we get a

constant function and we know that the derivative of a constant function is zero.

The first derivative of any function signifies the slope of the function. As the graph of

constant function is a horizontal line, its slope is zero, which justifies that the value of the

first derivative of the given function is 0.

Note: We can also solve the given question by actually differentiating each term of the

function using sum and product rule of differentiation. However, it will be time consuming.

Also, it’s better to simplify the function before finding its derivative as it’s easy to

differentiate a simple function instead of a complicated one.

simplifying the given function using properties of logarithmic function and then differentiating the terms given in the function using sum and product rule of differentiation.

To find the derivative of the function\[y={{\log }_{3}}x-{{\log }^{-1}}{{3}^{-1}}\times \log {{x}^{-1}}\], we will differentiate it with respect to the variable\[x\]using some logarithmic properties.

We will first simplify the given function.

We know that\[{{\log }_{b}}a=\dfrac{\log a}{\log b}\].

Substituting\[a=x,b=3\]in the above equation, we get\[{{\log }_{3}}x=\dfrac{\log x}{\log 3}\]. \[...(1)\]

We also know that\[{{\log }^{-1}}a=\dfrac{1}{\log a}\]. \[...(2)\]

Substituting\[a={{3}^{-1}}\], we get\[{{\log }^{-1}}{{3}^{-1}}=\dfrac{1}{\log {{3}^{-1}}}\].

\[...(3)\]

We know that\[\log {{a}^{-1}}=-\log a\].

Thus, we have\[\dfrac{1}{\log {{3}^{-1}}}=\dfrac{1}{-\log 3}\].

Merging the above equation with equation\[(3)\], we get\[{{\log }^{-1}}{{3}^{-1}}=\dfrac{1}{\log {{3}^{-1}}}=\dfrac{1}{-\log 3}\]. \[...(4)\]

Substituting\[a=x\]in equation\[(2)\], we get\[\log {{x}^{-1}}=-\log x\]. \[...(5)\]

Substituting equation\[(1)\], \[(4)\]and\[(5)\]in the given equation\[y={{\log }_{3}}x-{{\log }^{-1}}{{3}^{-1}}\times \log {{x}^{-1}}\], we get\[y={{\log }_{3}}x-{{\log }^{-1}}{{3}^{-1}}\times

\log {{x}^{-1}}=\dfrac{\log x}{\log 3}-\left( \dfrac{1}{-\log 3} \right)-\log x\].

Simplifying the above equation, we get\[y=\dfrac{\log x}{\log 3}-\dfrac{\log x}{\log 3}=0\].

We know that the differentiation of a constant function with respect to any variable is 0.

Thus, we have\[\dfrac{dy}{dx}=0\]as\[y=0\].

We get the derivative of the given function 0 as by simplifying the function, we get a

constant function and we know that the derivative of a constant function is zero.

The first derivative of any function signifies the slope of the function. As the graph of

constant function is a horizontal line, its slope is zero, which justifies that the value of the

first derivative of the given function is 0.

Note: We can also solve the given question by actually differentiating each term of the

function using sum and product rule of differentiation. However, it will be time consuming.

Also, it’s better to simplify the function before finding its derivative as it’s easy to

differentiate a simple function instead of a complicated one.

Last updated date: 26th Sep 2023

•

Total views: 365.1k

•

Views today: 5.65k

Recently Updated Pages

What do you mean by public facilities

Difference between hardware and software

Disadvantages of Advertising

10 Advantages and Disadvantages of Plastic

What do you mean by Endemic Species

What is the Botanical Name of Dog , Cat , Turmeric , Mushroom , Palm

Trending doubts

How do you solve x2 11x + 28 0 using the quadratic class 10 maths CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

One cusec is equal to how many liters class 8 maths CBSE

The equation xxx + 2 is satisfied when x is equal to class 10 maths CBSE

How many millions make a billion class 6 maths CBSE

How many crores make 10 million class 7 maths CBSE

What is meant by shramdaan AVoluntary contribution class 11 social science CBSE

One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE

How fast is 60 miles per hour in kilometres per ho class 10 maths CBSE